Induction of lactation in a patient with complete androgen insensitivity syndrome - Voon, Kimberly; Stuckey, Bronwyn G A (Endocrinology, diabetes & metabolism case reports, 2023)
With rising rates of adoption and surrogacy, induced lactation is likely to become increasingly relevant, allowing women who did not undergo pregnancy to breastfeed. We describe the case of a woman with complete androgen insensitivity syndrome (CAIS) on conventional oestrogen therapy who was expecting a child via surrogacy and who wished to breastfeed. The woman was commenced on supplementary oestrogen therapy, domperidone and breast stimulation by mechanical breast pump 8 weeks prior to the delivery of her child. Following delivery, the patient produced a small, unquantified amount of milk, allowing her to suckle the infant for a short period of time. Induced lactation is possible in chromosomally XY individuals. It has been most successful in cis-women and transwomen, both of whom have had progesterone/progestogen exposure to the breast. We suggest that the addition of a progestogen to our patient's treatment regimen, either as part of her original hormone therapy or part of the lactation induction program, would have improved her changes of establishing successful lactation.SummaryWith rising rates of adoption and surrogacy, induced lactation is likely to become increasingly relevant, allowing women who did not undergo pregnancy to breastfeed. We describe the case of a woman with complete androgen insensitivity syndrome (CAIS) on conventional oestrogen therapy who was expecting a child via surrogacy and who wished to breastfeed. The woman was commenced on supplementary oestrogen therapy, domperidone and breast stimulation by mechanical breast pump 8 weeks prior to the delivery of her child. Following delivery, the patient produced a small, unquantified amount of milk, allowing her to suckle the infant for a short period of time. Induced lactation is possible in chromosomally XY individuals. It has been most successful in cis-women and transwomen, both of whom have had progesterone/progestogen exposure to the breast. We suggest that the addition of a progestogen to our patient's treatment regimen, either as part of her original hormone therapy or part of the lactation induction program, would have improved her changes of establishing successful lactation.Induced lactation is possible in chromosomally XY individuals with the use of pharmacological and non-pharmacological therapies. There are no standardised guidelines regarding the optimal regimen for induced lactation. Progesterone exposure to the breast is essential for ductal branching and alveolar maturation. In the published literature, induced lactation is more successful in transwomen and other XY individuals who have had prior progesterone exposure. The addition of progestogen to our patient's treatment regimen would have improved her chances of establishing successful lactation.Learning pointsInduced lactation is possible in chromosomally XY individuals with the use of pharmacological and non-pharmacological therapies. There are no standardised guidelines regarding the optimal regimen for induced lactation. Progesterone exposure to the breast is essential for ductal branching and alveolar maturation. In the published literature, induced lactation is more successful in transwomen and other XY individuals who have had prior progesterone exposure. The addition of progestogen to our patient's treatment regimen would have improved her chances of establishing successful lactation.